Traditional Tuxtla Housing: Overlooked Heritage - Tondopó Mendoza , Yonalli (2025)
Tuxtla Gutiérrez is the capital city of the state of Chiapas, Mexico. Founded by Dominican friars in 1560, Tuxtla Gutiérrez began as a Zoque Indian village with four major neighborhoods: Santo Domingo, San Jacinto, San Andrés, and San Miguel. For many centuries, this settlement’s mainstay was traditional housing, a prevalent architecture. However, it began to be endangered in the 20th century, as demographic, urban, and economic growth led to its minimization and undervaluation by altering its material, stylistic, and architectural properties. It also changed its use from residential to commercial or mixed use, and in the most severe cases, its total disappearance. This document reviews traditional dwellings considered relevant in the city because they are registered in the National Catalog of Immovable Historical Monuments of the National Coordination of Historical Monuments of the National Institute of Anthropology and History. The intention is to highlight their current situation, which is unfavorable because unfortunately many of them only remain as documentary vestiges, having vanished from the city landscape.